(untitled) (Historia, 2021)
Dr Philip’s Empire: One Man’s Struggle for Justice in Nineteenth Century South Africa by novelist and historian Tim Keegan is the first full-length biography of the prominent nineteenth century missionary and humanitarian campaigner, John Philip, since Andrew Ross’s John Philip (1775-1851): Missions, Race and Politics in South Africa published in 1986. Born in Kirckcaldy, Scotland in 1775 and schooled in the principles and precepts of the Scottish Enlightenment, Philip took up residence in the Cape Colony in 1819 as the newly appointed superintendent of the London Missionary Society (LMS) in southern Africa. He remained a towering figure in the region, and beyond, for the remainder of his life, passing away in August 1851 at Hankey mission station amidst the turmoil of the eastern Cape frontier’s latest conflagration, in the form of the Eighth Frontier War (or Mlanjeni’s War) and the Kat River Rebellion. In a century marked by numerous turning points of lasting significance, the combined effects of the Eighth Frontier War and Kat River Rebellion risked undermining Philip’s vision for the Cape, in particular for its political future and race relations. Keegan delivers a comprehensive account of Philip’s illustrious evangelical-humanitarian career, skillfully weaving together the narrative thread of Philip’s life with insightful analysis of the context in which he operated, and which he influenced and was influenced by in turn. Indeed, the value of any historical biography lies in the biographer’s ability to shed light on the complexities, contingencies and contradictions that shaped the contours of the protagonist’s life, thus illuminating the historical context.